Antibodies targeting human endothelin-1 receptors reveal different conformational states in cancer cells - Herbet, A; Costa, N; Leventoux, N; Mabondzo, A; Couraud, J-Y; Borrull, A; Hugnot, J-P; Boquet, D (Physiological research, 2018)
The endothelin axis (endothelins and their receptors) is strongly involved in physiological and pathological processes. ET-1 plays a crucial role in particular in tumor diseases. Endothelin-1 receptors (ET(A) and ET(B)) are deregulated and overexpressed in several tumors such as melanoma and glioma. We studied the binding of 24 monoclonal antibodies directed against human ET(B) receptors (hET(B)) to different melanoma cell lines. Few of these mAbs bound to all the melanoma cell lines. One of them, rendomab B49, bound to ET(B) receptors expressed at the surface of human glioma stem cells. More recently, we produced new antibodies directed against human ET(A) receptor (hET(A)). Several antibodies have been isolated and have been screened on different tumoral cells lines. As for the mAbs directed against the hET(B) receptor only some of new antibodies directed against ET(A) receptor are capable to bind the human tumoral cell lines. Rendomab A63 directed against hET(A) is one of them. We report the specificity and binding properties of these mAbs and consider their potential use in diagnosis by an in vivo imaging approach.
Keywords: Animals; křečci praví; Female; CHO buňky; Cell Line, Tumor; ženské pohlaví; sekvence aminokyselin; Mice, Nude; vazba proteinů; Antibodies, Monoclonal; Receptor, Endothelin A; lidé; receptor endotelinu A; Mice; Amino Acid Sequence; Protein Binding; myši; Cricetulus; xenogenní modely - testy protinádorové aktivity; Xenograft Model Antitumor Assays; endotelin-1; receptor endotelinu B; monoklonální protilátky; Endothelin-1; zvířata; Endothelin A Receptor Antagonists; antagonisté endotelinového receptoru A; Receptor, Endothelin B; myši nahé; nádorové buněčné linie; Cricetinae; CHO Cells; Humans